The Effect Of Service Quality On Smart Parking User Satisfaction At PT. Mitragraha Inti Utama - Nur Latifah, Azzahra; Insani, Siti (Pascasarjana STIE Miftahul Huda, 2025)
This study aims to determine the extent of influence of Service Quality on Smart Parking User Satisfaction at PT Mitragraha Inti Utama. This research is a quantitative study, with a descriptive research objective. This type of research is causal. Meanwhile, the unit of analysis aimed at this study is individuals where smart parking users as respondents in the distribution of this research questionnaire. The sample in this study amounted to 100 respondents. Data were analyzed using validity tests, reliability, partial tests (t), simultaneous tests (f) and determination tests. Based on the results of the research in the reliability test, it was stated that each question was reliable, then based on partial and simultaneous tests the results of the study showed that Service Quality had a positive and significant effect on User Satisfaction. According to the results of the determination test, Service Quality on Smart Parking User Satisfaction at PT Mitragraha Inti Utama is classified as a high level, namely 84.8%, while the rest is influenced by other variables.